Predictors of early renal dysfunction after heart transplantation: a report from the International Consortium on Primary Graft Dysfunction. (3rd October 2022) - Guzman Bofarull, J; Han, J; Moayedi, Y; Truby, L K; Foroutan, F; Miller, R; Potena, L; Zuckermann, A; Chih, S; Farr, M; Hall, S; Ross, H J; et al.
Abstract: Background: Renal dysfunction is a common complication after heart transplantation (HT). Renal replacement therapy (RRT) after HT has been associated with increased risk of death. Long-term renal dysfunction is associated mainly to immunosuppressive therapy but is also strongly related to post-transplant renal failure. Predictors of early renal dysfunction after HT have not been clearly identified. Purpose: We aimed to define predictors of early renal dysfunction after HT. Methods: Our consortium includes 10 centers in the US, Canada and Europe. We collected data on all consecutive single-organ HT recipients from 2010 to 2020. The primary outcome was early renal dysfunction (ERD), defined as a composite of need for RRT or creatinine ≥2.5 mg/dL 24 hours after HT. We assessed the incidence of early renal dysfunction and performed univariate and multivariate analyses to identify the recipient and transplant characteristics associated with its development. Results: We included 2, 764 HT recipients: 282 (10.2%) presented early renal dysfunction and 2482 (89.8%) did not. Recipients who presented postoperative renal dysfunction were more frequently male, Caucasian, with previous sternotomy, higher baseline creatinine, longer ischemic time and worse donor LVEF. They were also more likely to be under RRT, intravenous inotropes or ECMO support and there was more incidence of severe primary graft dysfunction (PGD) (Table 1). Multi-variable logistic regression demonstrated that the strongest predictors for post-transplant renal dysfunction were development of severe PGD (OR 5.26, 2.88–9.62, p<0, 001) and RRT prior to HT (OR 5.80, 2.93–11.5, p<0.001). Other predictors were male sex, previous sternotomy, long ischemic time and need for inotropes prior to HT. Conclusions: Early renal dysfunction is a common complication after HT with an incidence around 10% in a large and contemporary cohort. The presence of PGD and need for RRT pre-transplant were the strongest predictors for its development. Interestingly, emergent transplantation or need for MCS were not independently associated with ERD. Further studies are needed to identify patients at high risk of early and late kidney dysfunction that may benefit from combined transplantation. Funding Acknowledgement: Type of funding sources: None.